If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15m + 22 = -7n + 18 Reorder the terms: 22 + 15m = -7n + 18 Reorder the terms: 22 + 15m = 18 + -7n Solving 22 + 15m = 18 + -7n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 15m = 18 + -22 + -7n Combine like terms: 22 + -22 = 0 0 + 15m = 18 + -22 + -7n 15m = 18 + -22 + -7n Combine like terms: 18 + -22 = -4 15m = -4 + -7n Divide each side by '15'. m = -0.2666666667 + -0.4666666667n Simplifying m = -0.2666666667 + -0.4666666667n
| 14x^2+24x+2=0 | | 15x^2+24x+2=0 | | 10x^2+12x+2=0 | | 5x(4x+6)=I | | 4b+19= | | 12+x=9-2x | | -34=5(w-8)-8w | | 5x-7=-8x+4 | | -9(3b+4)+(28-3)=0 | | 360=k/36 | | 7y+18=9y+12 | | r=7.63/2(3.14) | | 9(3b+4)+(28b-3)=0 | | 987654321=621 | | X/3-2x-8/5=8/3 | | 3x/4-x-7/6=7/4x | | Y=-.2x-13 | | 9y-8x=72x | | 11/4x=66 | | y(1-x)=0 | | 3x+7=14-4x | | 3y-12=16+y | | X/2-x/3=10 | | x+7/4=66 | | f(x)=3x^11-7x^9+11 | | (1-x)y=0 | | -(4y+1)-(-3y-5)=-3 | | 4m-6m=-6m-12 | | (2-x)-(7-3x)=55+6x | | (2-10x^2+8x^4)/((x^2+3)^2) | | 4y+13=12-2y | | y=v(1-x) |